2007
DOI: 10.1086/512476
|View full text |Cite
|
Sign up to set email alerts
|

The Compact, Conical, Accretion‐Disk Warm Absorber of the Seyfert 1 Galaxy NGC 4051 and Its Implications for IGM‐Galaxy Feedback Processes

Abstract: Using a 100 ks XMM-Newton exposure of NGC 4051, we show that the time evolution of the ionization state of the X-ray absorbers in response to the rapid and highly variable X-ray continuum constrains all the main physical and geometrical properties of an AGN ''warm absorber'' wind. The absorber consists of two different ionization components, with a difference of %100 in ionization parameter and %5 in column density. By tracking the response in the opacity of the gas to changes in the ionizing continuum, we wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
274
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(300 citation statements)
references
References 74 publications
20
274
6
Order By: Relevance
“…In the following calculations, we adopt the "prescriptions" of Tombesi et al (2012a) and Crenshaw & Kraemer (2012); see also Krongold et al (2007) and Pounds & Reeves (2009) for additional discussion of outflows and related geometry.…”
Section: Radio Datamentioning
confidence: 99%
“…In the following calculations, we adopt the "prescriptions" of Tombesi et al (2012a) and Crenshaw & Kraemer (2012); see also Krongold et al (2007) and Pounds & Reeves (2009) for additional discussion of outflows and related geometry.…”
Section: Radio Datamentioning
confidence: 99%
“…Variability studies could, in principle, allow us to estimate the location and geometry of the absorber (Nicastro et al 1999;Krongold et al 2007;Risaliti et al 2005;Reeves et al 2008), thereby placing more stringent limits on the remaining large (order of magnitude) uncertainties in the total mass, energy and momentum that is driven by these outflows (Elvis 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Such wind would be ubiquitous in AGN but only visible when the gas crosses our line of sight (Goodrich & Miller 1995;Hines & Wills 1995;Murray et al 1995;Elvis 2000;. It has also been suggested that the same gas may be responsible for absorption and emission (e.g., Mathur et al 1995;Elvis 2000;Fields et al 2005;Krongold et al 2007;Andrade-Velazquez et al 2010;Longinotti et al 2013;Miniutti et al 2014;Sanfrutos et al 2016), or that BALs may be associated to the obscuring dusty torus (Leighly et al 2015). However, other scenarios suggest that the incidence of BALs may be related to evolutionary phases (Hazard et al 1984;Becker et al 2000) and that mini-BALs and BALs may represent the same outflow but at different evolutionary stages (Hamann & Sabra 2004).…”
Section: Introductionmentioning
confidence: 95%